Nanoplasmonic-gold-cylinder-array-enhanced terahertz source - 敖志光 孙金海 蔡禾 宋国峰 宋甲坤 宋玉志 徐云 (Journal of semiconductors, 2016)
Photoconductive antennas （PCAs） based on nanoplasmonic gratings contact electrodes have been pro- posed to satisfy the demand for high power, efficiency and responsivity terahertz （THz） sources. Reducing the average photo-generated carrier transport path to the photoconductor contact electrodes was previously considered the dominant mechanism to improve PCAs＇ power. However, considering the bias in a real device, the electric field between gratings is limited and the role of surface plasmonic resonance （SPR） field enhancement is more important in improving THz radiation. This paper, based on SPR, analyzes the interaction between incident light and substrate in nano cylinder array PCAs and clearly shows that the SPR can enhance the light absorption in the substrate. After the optimization of the structure size, the proposed structure can offer 87% optical transmission into GaAs substrate. Compared with conventional PCAs, the optical transmission into the substrate will increase 5.8 times and the enhancement factor of substrate absorption will reach 13.7 respectively.